INNOVATIVE WAYS OF ORGANIZING ASSESSMENT ACTIVITIES IN THE DIGITAL ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract:  This  article  examines  innovative  ways  of  organizing  valuation activities in the digital economy. The article also examines the issues of forming and developing valuation activities as a condition for ensuring the civilized regulation and transparency of digital economic relations in the context of the formation of a digital economy  in  the  economy  of  our  republic,  the  expansion  of  the  processes  of privatization,  denationalization,  structural  transformation  and  corporatization  of enterprises,  the  attraction  of  foreign  capital,  the  expansion  of  various  types  of operations  carried  out  with  property  and  non-property  rights,  the  development  of market mechanisms of economic management.